(untitled) (Tanzania Medical Journal, 2022)
Background Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for several difficult-to- treat infections than ordinary staphylococcal infections. It is associated with an increased hospital stay, mortality, and morbidity. Evidence shows that hospital janitors act as an important reservoir of MRSA, which if left undetected, may contribute to its spread. This study determines the colonization rates of Staphylococcus aureus and MRSA together with their antimicrobial sensitivity among hospital janitors in the central zone of Tanzania. Methodology This was a baseline report from a quasi-experimental hospital-based study that was conducted in central Tanzania, involving 122 hospital janitors selected using a systemic random sampling from three regional hospitals. Nasal swabs were collected, pre-enriched, and inoculated into blood and mannitol agar plates. The confirmation of MRSA was done using a cefoxitin disc, and the antibiotic susceptibility test was done using the disc diffusion. SPSS was used for analysis; descriptive statistics were employed; a chi square coefficient was reported; and a p-value of ≤ 0.05 was considered statistically significant. Results The prevalence of Staphylococcus aureus was 21% (25/119); among them, MRSA was 44% (11/25). The colonization was more common among females (23.1% vs. 17.1%), with a low education level (25% vs. 17.5%), with working experience of two years or more (26.5% vs 17.5%), and those who were cleaning in the laboratory (28.6% vs. 14.3% in the office). Clindamycin was effective against the majority of Staphylococcus aureus isolates (20/25) tested positive. MRSA isolates were more likely than Methicillin-Susceptible Staphylococcus aureus to be resistant to many antimicrobial drugs tested (p < 0.001). The multi-drug resistance was 36%, and it was higher among the MRSA (81.8%) isolates than the MSSA (p <0.001). Conclusion There is a high prevalence of nasal colonization with Staphylococcus aureus and MRSA among hospital janitors. Most Staphylococcus aureus isolates were sensitive to clindamycin. The MRSA isolates were resistant to many antimicrobial drugs compared to the MSSA. Findings suggest that hospital janitors may contribute to spreading MRSA if they do not observe proper hygienic practices. Therefore, efforts should be made to ensure they are adhering to infection prevention and control measures while working.